MOTIVASI PETANI DALAM PENERAPAN PEMUPUKAN TANAMAN KAKAO (Theobroma cacao L.) DI KECAMATAN BIRU - BIRU KABUPATEN DELI SERDANG - Nurul Hidayah Hasibuan; Fahruddin Nasution (Agrica Ekstensia, 2020)
The purpose of this research is to determine the level of motivation (economic motivation and sociological motivation) of farmers and the relationship of motivation factors with the level of farmers motivation in the application of cocoa plants cultivation (Theobroma cacao L.) because high levels of motivation and good crop fertilization correlate with increased production. This research was conducted in Biru-Biru District, Deli Serdang Regency in April until May, 2018. Data collection method was used by observation and interview method using questionnaires that have been tested for its validity and reliability, where farmers who become research samples as 35 farmers with the characteristics of selected farmers have joined the cocoa farming group, active in farming groups, have the potential in cocoa cultivation and have received counseling materials on fertilizing cocoa crops and data analysis method using Likert scale and rank spearman correlation with the help of SPSS for windows program 18. The results showed that the level of motivation of farmers in the application of cocoa cultivation (economic motivation is very high that is 95.42 percent and the level of high sociological motivation is 76.57 percent), while the results of rank spearman correlation to factors related to farmer motivation there is a relationship which is significant between age, non-formal education, experience, income, wide land use, availability of production means, market guarantees and technology packages on economic motivation and there is a significant relationship between age, non-formal education and farm credit availability to sociological motivation.